2004
DOI: 10.1111/j.1442-9071.2004.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenomas of the lacrimal gland: a clinicopathological analysis

Abstract: Pleomorphic adenomas of the lacrimal gland may present with duration of symptoms of less than 10 months. Cystic degeneration, squamous metaplasia, calcification or ossification may be observed in lacrimal gland pleomorphic adenomas, as has been described in pleomorphic adenomas of salivary glands. However, the presence of calcification and bone erosion radiologically in a lacrimal gland tumour does not necessarily indicate malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Sen and coworkers8 analysed a series of 32 cases of LGPA and found that the duration of symptoms was less than 10 months in 28% of cases. Calcification of the tumour, usually considered a sign of malignancy, has also been described in LGPA3 9 10 and there is a report of a case with bone destruction 11.…”
Section: Discussionmentioning
confidence: 99%
“…Sen and coworkers8 analysed a series of 32 cases of LGPA and found that the duration of symptoms was less than 10 months in 28% of cases. Calcification of the tumour, usually considered a sign of malignancy, has also been described in LGPA3 9 10 and there is a report of a case with bone destruction 11.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous metaplasia within the lacrimal gland may be found in pleomorphic adenoma 8 . Microscopy in this case did not suggest the presence of an underlying lesion and we believe that the characteristic features of infarcted glands with preserved architecture, fibrosis and vascular thrombosis justify the diagnosis of NS or, in the case of the lacrimal gland, necrotizing dacryometaplasia.…”
Section: Histologymentioning
confidence: 53%
“…In 2 previous reports on lacrimal gland tumours from our centre, cystic changes were found in 4% cases (2 out of 50 cases) on imaging and cystic degeneration in 36% and 16% cases on histopathology, respectively. 4,5 Preoperative differentials in cystic pleomorphic adenomas of salivary gland usually are lymphoepitheloid cyst, mucocele, and pseudocysts from a neoplastic lesions such as Warthin's tumour and adenocarcinoma. According to the incidence of lacrimal gland tumours, the possible differentials in cases with multicystic appearance are pseudocysts within a tumour-like adenoid cystic carcinoma, adenocarcinoma, carcinoma ex pleomorphic adenoma, and rarely benign lesions such as dacryops or cystadenoma.…”
Section: Cystic Pleomorphic Adenoma Of the Lacrimal Gland: A Clinicopmentioning
confidence: 99%